The Effectiveness of Scheduling Activities to Reduce the Intensity of Playing Online Games in Children - Afitria Rizkiana (Universitas Muhammadiyah Ponorogo, 2023)
The problem of online game addiction harms children. One of the negative impacts of online game addiction is related to schools, so special treatment is needed. The subjects who participated in this study were those who were diagnosed with online game addiction problems. Assessments carried out to diagnose subjects included interviews, observations, and the Video game Addiction Scale for Children. The intervention used is scheduling activities. The intensity of the subject's online game playing was reduced after the intervention was given. The duration of playing online games was originally an average of 2.4 hours per day in 1 week, after the intervention, it became 0.4 hours per day in 1 week. Subjects spend more time studying, doing homework, fishing or sleeping during the day. The score of the Video game Addiction Scale for Children also changed from 83 (high) to 58 (medium).